Current Practices Surrounding Endonasal Skull Base and Pituitary Surgery during COVID-19 Pandemic: A Global Survey. (16th November 2020) - Champagne, Pierre-Olivier; McDowell, Michael M; Wang, Eric; Snyderman, Carl H; Zenonos, Georgios A; Gardner, Paul A
Abstract: INTRODUCTION: During the Sars-CoV-2 pandemic, Endoscopic Endonasal Surgery (EES) is feared to be a high-risk procedure for transmission of the COVID-19 virus. Nonetheless, data are lacking regarding the management of EES during this pandemic. METHODS: A web-based survey of skull base surgeons worldwide was conducted. Different practices by geographical regions and COVID-19 prevalence were analyzed. RESULTS: 135 unique responses were collected. Regarding the use of personal protection equipment (PPE), North America reported using more powered air-purifying respirators (PAPR) and Asia/Europe using more standard precautions. North America and Europe resorted more to reverse transcriptase polymerase chain reaction (RT-PCR) for screening asymptomatic patients. High prevalence countries showed a higher use of PAPR. The medium prevalence group reported lower RT-PCR testing for symptomatic cases and the high prevalence group used it significantly more in asymptomatic cases. 19 respondents reported healthcare personnel transmission of COVID-19 from EES, with a higher rate of transmission among countries classified as having a medium prevalence of COVID-19. These specific respondents (medium prevalence) also reported a lower use of airborne PPE. In the cases of healthcare transmission, the patient was reportedly asymptomatic 32% of the time. CONCLUSION: This survey gives an overview of EES practices during the Sars-CoV-2 pandemic. Intensified preoperative screening, even in asymptomatic patients, RT-PCR for all symptomatic cases, and an increased use of airborne PPE is associated with decreased reports of COVID-19 transmission during EES.